Tipologi dan Potensi Sub Sektor Pertanian di Kabupaten Gianyar - YOHANES FACRIS BANI; I WAYAN BUDIASA; I WAYAN WIDYANTARA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Typology and Potential of Agricultural Sub-Sector in Gianyar Regency The lowest contribution in the formation of GRDP in Gianyar Regency in 2017 by theagricultural category was 12,84 percent (decreased from 13,06 percent in 2016. Thepurpose of this study was to determine the position of each agricultural sub-sector, baseand non-base sub-sectors in the economy in Gianyar Regency Research location wasdetermined deliberately. The research method used the Klassen typology analysismethod and Location Quetient with timeseries PDRB data for the last five years (20132017).The results of the Tiplogi comparison were food crop sub-sector, horticultureplant sub-sector annual seasonal plantations and sub-sectors included in theclassification of the potency sub-sector or can still develop, while the other agriculturalsub-sectors are in the relatively underdeveloped sub-sector classification, thehorticulture plant sub-sector a year, annual plantation sub-sector, livestock sub-sectorand sub-sector agricultural services and hunting. The results of the location quotient aresub-sectors which are the basic sub-sectors in the economy of Gianyar Regency, namelythe food crop sub-sector, annual horticulture sub-sector, and the annual plantation subsector.While the horticultural plant sub sector a year, the annual plantation sub-sector,the livestock sub-sector and the agriculture services and hunting sub-sector are non-basesub-sectors in the economy of Gianyar Regency. The development of agriculturalcommodities must have strategic characters, such as being oriented to market demandand concentrated on superior products with high competitiveness.